Organic salt photovoltaics. Issue 5 (2nd May 2017) - Bates, M.; Lunt, Richard R.
Abstract : A review of organic salt based photovoltaics highlighting unique and ionic properties for organic and transparent photovoltaics, including deep NIR absorption and independently tunable molecular orbitals. Abstract : In this article we review the development of organic salts integrated in organic photovoltaics (OPVs) and the potential capabilities that organic salts enable in OPV devices. Organic salts are ionic compounds composed of either organic cations, anions, or a combination of both. These organic salt semiconductors can exhibit highly tunable properties with absorption throughout the visible and deep into the near-infrared. These characteristics have enabled their integration into traditional OPV cells, multijunctions, and transparent photovoltaic devices with unique applications for windows and similar surfaces. We discuss the tunable properties of these salts that make them desirable for use in a range of applications and the historical development of salt based OPVs to provide an overview of the progress made in efficiencies and device architectures. Among their most exciting properties, organic salts have the ability to enable high efficiency transparent photovoltaics (TPVs), tunable energetics, and highly efficient ultra-deep infrared harvesting.